Human Resource Management Training To Improve The Performance Of Social Organizations In Optimizing Community Empowerment Programs: Pelatihan Manajemen Sumber Daya Manusia Untuk Meningkatkan Kinerja Organisasi Sosial Dalam Mengoptimalkan Program Pemberdayaan Masyarakat - Aggy Pramana Gusman; Andrianof, Harkamsyah; Andrica Putra, Okta (Journal of Community Service and Application of Science, 2024)
Human resource management (HR) training is very important in improving the performance of social organizations in society. In Koto Parak Padang Village, many social organizations focus on community empowerment, but most face obstacles in effective human resource management. Therefore, this community service aims to provide training to managers and members of social organizations in Koto Parak Padang Village about the basic principles of HR management and ways to optimize organizational performance. This training covers topics such as HR planning, recruitment, training, career development, and performance evaluation. Apart from that, participants are also trained in managing conflict and building effective communication in social organizations. The method used in this service is a participatory approach, where participants are actively involved in group discussions and share experiences. Data is collected through surveys and interviews to determine more specific training needs and to evaluate changes after training. The expected result of this activity is an increase in the capacity of managers and members of social organizations in managing human resources more professionally, which in turn can increase the effectiveness of the community empowerment programs being implemented. Thus, it is hoped that this training can make a significant contribution to social and economic development in Koto Parak Padang Village.